2020
DOI: 10.1103/physrevmaterials.4.025002
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between crystal purity and the charge density wave in 1TVSe2

Abstract: We examine the charge density wave (CDW) properties of 1T -VSe2 crystals grown by chemical vapour transport (CVT) under varying conditions. Specifically, we find that by lowering the growth temperature (T g < 630 • C), there is a significant increase in both the CDW transition temperature and the residual resistance ratio (RRR) obtained from electrical transport measurements. Using xray photoelectron spectroscopy (XPS), we correlate the observed CDW properties with stoichiometry and the nature of defects. In a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…Given these promising results, we believe it is worthwhile to develop and refine combined ultrafast techniques. Our approach can be employed to investigate the detailed mechanisms driving the phase transitions in a wide range of strongly correlated materials [70][71][72].…”
Section: Discussionmentioning
confidence: 99%
“…Given these promising results, we believe it is worthwhile to develop and refine combined ultrafast techniques. Our approach can be employed to investigate the detailed mechanisms driving the phase transitions in a wide range of strongly correlated materials [70][71][72].…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is supported by reports from both chemical vapour transport (CVT) crystal growth of TMDs and CVD growth utilising W(CO) 6 as the W source [8,20,52]. In the case of CVT growth, studies have shown that the materials suffer from a natural chalcogen deficiency due to the volatility of the chalcogen atoms [53,54]. To alleviate this, CVTproduced TMDs are deliberately grown with a stoichiometric ratio greater than 2:1 (chalcogen: metal).…”
Section: Resultsmentioning
confidence: 94%
“…The preparation and characterisation of single crystals of VSe 2 are extensively reported in Ref. [16]. In summary, it was reported that in order to obtain near ideal stoichiometry and to minimise the presence of defects, samples were prepared by chemical vapour transport at a growth temperature of 550 • C. Electrical transport measurements show a residual resistance ratio or RRR = 49 and a CDW transition temperature, T c = 112.7 K. The work reported here was carried out on a single crystal with approximate dimensions of 2 × 3 mm.…”
Section: Methodsmentioning
confidence: 99%
“…For example, angle resolved photoemission and scanning tunnelling spectroscopy experiments report gap sizes varying between 13 to 130 meV [7,8,11,14,15]. Recently, some of us reported the sensitivity of the CDW properties to defects and overall stoichiometry [16]. It was demonstrated that depending on sample growth conditions the defects and Se deficiencies proliferate, while optimal growth conditions can be achieved to produce stoichiometric, clean crystals with an enhanced critical transition temperature for the CDW phase.…”
Section: Introductionmentioning
confidence: 99%